Design of Embedded Terminal Data Remote Transmission Control System in Internet of Things. Issue 1 (January 2020) - Fu, Weiqing; Yang, Minglai
Abstract: The underlying data exchange system of the Internet of Things is an integrated system for data collection and information transmission of the Internet of Things. The design method of the underlying data exchange system of the Internet of Things based on embedded is proposed. The embedded data remote acquisition system designed in this paper, the main communication control module and data acquisition and processing module are relatively independent. The embedded microcontroller AT89S52 is used to realize the main data transmission function. In the hardware design, the selection of A/D analog-to-digital converter is fully considered. A scheme of remote monitoring system based on the combination of communication network and Internet is proposed, and an embedded system based on DSP chip is further selected to design and implement the data transmission terminal of the remote monitoring system. Combined with Visual DSP++4. 5 development platform, the integration processing and information processing of the Internet of Things bottom data are carried out. The VIX bus transmission foundation is adopted to realize the data exchange control of the Internet of Things bottom, and the hardware design and software development of the system are completed. The test results show that the stability of data exchange at the bottom of the Internet of Things is good and the output error rate of data exchange is low.